Drought monitoring: Mali - Dembélé, Moctar; Koné, A.; Amarnath, Giriraj; Zwart, Sander; Schmitter, Petra (International Water Management Institute, 2025)
The Mali Drought Monitoring System (MaliDMS) helps monitor drought onset, occurrence, duration, extent and severity based on WaPOR-derived and other high resolution remote-sensing data that are generated in near real time to enable a comprehensive assessment of drought conditions.